Tantangan dan Keamanan Teknologi Informasi pada Manajemen Bank Syariah - Abdullah Mubarak Lubis; Gladis Jelita; Syafira Okta Vionna Wirya; Nurbaiti Nurbaiti (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
Information technology (IT) has become a key element in the development of the financial industry, including Islamic banking. A primary challenge for IT management in Islamic banks is data security from cybercrime, which can damage the bank’s reputation and customer trust. This study aims to further examine the challenges and efforts that Islamic banks can undertake to enhance IT security. The research methodology uses a qualitative approach with descriptive methods and literature review to describe the phenomenon in depth based on data and information from various relevant literature sources. The study’s findings show that Islamic banks need to strengthen security through encryption, continuous monitoring, and employee training on cybersecurity. The conclusion of this study recommends that Islamic banks continue to raise awareness among employees and customers about security risks and ensure regulatory compliance. This research is expected to serve as a reference for Islamic banks in maintaining information security in the digital era.